PEMAKNAAN GAYA HIDUP DALAM TVC DJI SAM SOE MAGNUM FILTER VERSI FERRY - Murtani, Hanafi; Lamanda, Ni Putu Frinchika (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2015)
One of the media used in advertising Dji Sam Soe Magnum Filter is television. Television is one of the media in advertising that uses color, sound, movement and music, or can be referred to as an audio-visual medium, so it can also be to determine the meaning of a lifestyle that is contained in the visualization TVC Dji Sam Soe Filter ver-sion Ferry Magnum. This study aims to determine the meaning of a lifestyle that is contained in the visualization TVC Dji Sam Soe Filter version Ferry Magnum. These include: To find out the myth that contained about lifestyle in TVC Dji Sam Soe Filter version Ferry Magnum. The method used is qualitative analysis approach semiology of Roland Barthes. From the analysis it can be concluded, meaning contained lifestyle of advertising Dji Sam Soe Ferry Magnum version of the filter is reflected Luxury lifestyle, where luxury lifestyle is a lifestyle activities to seek pleasures, such as spending more time outside the home, more play , happy in the city crowd, happy to buy expensive goods pleases, and always wanted to be the center of attention. Set of meanings contained in the ad-vertisement gives the sense that the purpose of Magnum Filter Cigarettes are cigarettes represent young children luxurious lifestyles, and modern. Because during the myths that developed in the community is, cigarettes are very closely with the image of smokers: the elderly, people of the village. However Magnum Filter change peopleâs views about the lifestyle of todayâs clove smokers luxurious and exclusive.